Quantitative trait loci for resistance to Fusarium head blight in the Chinese wheat landrace Huangfangzhu - Li, Tao; Bai, Guihua; Wu, Shuangye; Gu, Shiliang (My University, 2012)
The Chinese wheat landrace Huangfangzhu (HFZ) has a high level of resistance to Fusarium head blight (FHB). To identify chromosomal regions that are responsible for FHB resistance in HFZ, F8 recombinant inbred lines (RIL) were developed from a cross between HFZ and Wheaton, a U.S. hard spring wheat. FHB was evaluated by single floret inoculation in both greenhouse and field environments. Two quantitative trait loci (QTL) with major effects were identified. One QTL was located on the short arm of chromosome 3B, and explained 35.4% of the phenotypic variation; the other QTL was assigned to 7AL and explained 18.0% of the phenotypic variation for FHB response. In addition, three minor QTL were detected on chromosomes 1AS, 1B and 5AS by single marker regression. HFZ contributed all favorable alleles. The RIL with HFZ alleles at the QTL on 3BS and 7AL displayed significantly lower percentages of infected spikelets than RIL without these alleles in both greenhouse and field environments. HFZ combined several alleles from germplasm reported previously and is a promising alternative source for improving wheat FHB resistance.
Citation: Li, T., Bai, G., Wu, S. et al. Euphytica (2012) 185: 93. https://doi.org/10.1007/s10681-012-0631-2
Keywords: Head scab; Wheat landrace; Fusarium head blight resistance; Quantitative trait loci; Genetic effects